The Company Store and the Literally Captive Market: Consumer Law in Prisons and Jails - Raher, Stephen (2020)
The growth of public expense associated with mass incarceration has led many carceral systems to push certain costs onto the people who are under correctional supervision. In the case of prisons and jails, this frequently takes the form of charges and fees associated with telecommunications, food, basic supplies, and access to information. Operation of these fee-based businesses (referred to here as “prison retail”) is typically outsourced to a private firm. In recent years, the dominant prison retail companies have consolidated into a handful of companies, mostly owned by private equity firms. This paper explores the practices of prison retailers, and discusses potential consumer-law implications. After an overview of the prison-retail industry and a detailed discussion of unfair practices, the paper looks at some potential legal protections that may apply under current law. These protections, however, prove to be scattered and often illusory due to mandatory arbitration provisions and prohibitions on class adjudication. The paper therefore concludes with recommendations on a variety of steps that state, local, and federal governments can take to address the problems inherent in the current model